PENGARUH TINGKAT PENDAPATAN DAN TINGKAT PENDIDIKAN TERHADAP PERILAKU KONSUMTIF WANITA KARIR DI LINGKUNGAN PEMERINTAH PROVINSI RIAU - Ikhwani Ratna; Hidayati Nasrah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Consumptive behavior today is a phenomenon that is prevalent in many societies. No exception career woman to do the job requires a supporting infrastructure. But in fulfilling these needs are often trapped in Consumptive behavior. The purpose of this study was to analyze the effect of educational level and income level of the Consumptive behavior of career women in the Provincial Government of Riau. This study uses multiple linear regression analysis. To determine the influence of independent variables on the dependent variable partially used t test, whereas to determine the effect of independent variables on the dependent variable simultaneously used F test research population is all women career civil servant status and positions in the Riau Provincial Government amounted to 365 people. While the number of samples using Slovin formula and obtained a sample of 78 people. Data obtained using questionnaires, analyzed with regression at α = 0:05. The results showed that simultaneous two variables level of education and income levels significantly influence Consumptive behavior with α significance level of 0.002. And a variable level of education is partially no effect on Consumptive behavior with α significance level of 0.632, while the variable income levels partially significant effect on Consumptive behavior with α significance level of 0.005.